Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0153449
|View full text |Cite
|
Sign up to set email alerts
|

Complex Minigene Library Vaccination for Discovery of Pre-Erythrocytic Plasmodium T Cell Antigens

Abstract: Development of a subunit vaccine targeting liver-stage Plasmodium parasites requires the identification of antigens capable of inducing protective T cell responses. However, traditional methods of antigen identification are incapable of evaluating T cell responses against large numbers of proteins expressed by these parasites. This bottleneck has limited development of subunit vaccines against Plasmodium and other complex intracellular pathogens. To address this bottleneck, we are developing a synthetic minige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 68 publications
(66 reference statements)
0
15
0
Order By: Relevance
“…With respect to such Ag discovery, our study additionally demonstrated a novel method for rapidly evaluating candidate Ags and for making Go/No Go decisions about their protective potential. Immunogenicity testing is fraught with misleading outcomes because many Ags are immunogenic in immunized animals but are ultimately nonprotective (30,36,91). In the DNA-only acute challenge model described in this article (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to such Ag discovery, our study additionally demonstrated a novel method for rapidly evaluating candidate Ags and for making Go/No Go decisions about their protective potential. Immunogenicity testing is fraught with misleading outcomes because many Ags are immunogenic in immunized animals but are ultimately nonprotective (30,36,91). In the DNA-only acute challenge model described in this article (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For all vaccinations, a plasmid encoding the Escherichia coli heat-labile lymphotoxin (LT) (29) was used as an adjuvant in a 1:10 ratio with the CSP-minigene vector. DNA was purified using an endotoxin-free purification kit (Qiagen), loaded onto gold beads (1-2-mm diameter; InBio Gold), and coated on tubing as cartridges for helium gas-propelled bombardment via gene gun on trimmed abdominal skin as described previously (30). Mice were vaccinated using a PowderJect-style gene gun by cluster priming for the first DNA vaccination using two cartridges (0.5 mg DNA per cartridge), each 2 d apart as shown in the figures (hereafter called "cluster primed" and denoted in figures with a " + "), and were boosted a single day later as indicated using two cartridges.…”
Section: Dna Vaccination By Gene Gunmentioning
confidence: 99%
“…Cartridges were loaded using traditional methods [28] . Cartridge batches were quality controlled by elution of single cartridges with 50 µL of water and quantified for DNA concentration using a NanoDrop (Thermo Scientific, Waltham, MA).…”
Section: Methodsmentioning
confidence: 99%
“…GG DNA immunization has been successfully utilized in vaccination trials for viral and neoplastic diseases in humans, primates, pigs and mice, and was recently used in mice to discover new Plasmodium yoelii sporozoite candidate antigens [22] , [25] , [27] , [28] . To our knowledge, GG DNA immunization using complex protozoal antigens has never been tested in a large, outbred species such as cattle.…”
Section: Introductionmentioning
confidence: 99%
“…DC and CTL cells play a key role in viral clearance during the immune process, so it is important to induce vaccines that produce strong, long-lasting, cross-T cell responses [319][320][321][322]. This minigene can express a segment of amino acid residue peptide through viral infection or the synthesis of a minigene.…”
Section: Covid-19 Synthetic Minigene Vaccinementioning
confidence: 99%